RECLAIMING THE FUTURE: KNOWLEDGE, POWER, AND JUSTICE REWRITTEN - Muhammad Zaynul Abrori (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the relationships between knowledge, power, and justice within education systems and local governance. It employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, focus group discussions (FGDs), and document analysis, and subsequently analyzed using thematic analysis. The findings indicate that the dominance of formal knowledge leads to the epistemic exclusion of local knowledge, while the centralization of power creates disparities in access and community representation in decision-making processes. Consequently, community participation tends to be merely symbolic, and local knowledge has not received adequate recognition within the formal system. The study concludes that strengthening epistemic justice requires recognizing the plurality of knowledge, substantially increasing community participation, and fostering more inclusive governance. These findings are expected to inform the development of more democratic and equitable education and governance policies.